2020
DOI: 10.1101/2020.12.23.20248761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forecasting intensive care unit demand during the COVID-19 pandemic: A spatial age-structured microsimulation model

Abstract: BackgroundThe COVID-19 pandemic poses the risk of overburdening health care systems, and in particular intensive care units (ICUs). Non-pharmaceutical interventions (NPIs), ranging from wearing masks to (partial) lockdowns have been implemented as mitigation measures around the globe. However, especially severe NPIs are used with great caution due to their negative effects on the economy, social life and mental well-being. Thus, understanding the impact of the pandemic on ICU demand under alternative scenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…A.2 , mobility increased predominantly in states and counties in the north and east of Germany where the COVID-19 incidence remained at an extremely low level throughout the summer months. This explanation is consistent with the modeling results by Klüsener et al (2020) that there was room for further relaxing NPIs in Germany during the summer months due to the weak dynamics of the pandemic in this period.…”
Section: Resultssupporting
confidence: 92%
“…A.2 , mobility increased predominantly in states and counties in the north and east of Germany where the COVID-19 incidence remained at an extremely low level throughout the summer months. This explanation is consistent with the modeling results by Klüsener et al (2020) that there was room for further relaxing NPIs in Germany during the summer months due to the weak dynamics of the pandemic in this period.…”
Section: Resultssupporting
confidence: 92%
“…A higher ICU occupancy rate by COVID-19 patients was correlated with higher excess mortality, which indicates that ICU capacity and the preparedness of the health care system contributed substantially to the spatial variation in the burden of the COVID-19 pandemic. 31 , 32 While the cumulative numbers of confirmed COVID-19 cases had a significant effect on the excess mortality cumulated over the study period, a correlation between weekly confirmed COVID-19 cases and weekly excess mortality was not observed for the northern federal states of Bremen, Hamburg, Lower Saxony and Schleswig-Holstein. This result may be explained by the differences in the testing strategies of the federal states.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, gatherings in public places were limited to members of two households. On December 16, the lockdown was extended to the nationwide closure of schools, childcare facilities, and nonessential shopping (Klüsener et al, 2020 ). The second lockdown continued to be in place until April 2021.…”
Section: Introductionmentioning
confidence: 99%